Stability analysis of totally positive switched linear systems with average dwell time switching. (May 2020) - Wang, Guosheng; Liu, Yang; Lu, Jianquan; Wang, Zhen
Abstract: This paper investigates the stability of totally positive switched linear systems (TPSLSs), for the continuous-time case and the discrete-time case. The multiple linear copositive Lyapunov function (MLCLF) is used to study exponential stability of the considered system with average dwell time. Then the case with common linear copositive Lyapunov function (CLCLF) is also established. Sufficient conditions to ensure the stability are given. Finally, numerical examples are presented to validate the efficiency of the derived results.